Spin-Dependent effects in helical molecular systems with rashba-like spin-orbit interaction - Gutierrez, Rafael; Cuniberti, Gianaurelio (Giovanni) (Acta Physica Polonica A, 2015)
Strong spin-selective effects have been recently observed in both photoemission and electrical transport experiments in biomolecular systems, opening fascinating possibilities for interfacing semiconductor and biomolecular systems to create highly efficient spintronics devices. From the theoretical and experimental point of view there are strong suggestions that molecular chirality is playing a crucial role. In this study we extend a previously formulated model (R. Gutierrez, E. Díaz, R. Naaman, G. Cuniberti, Phys. Rev. B 85, 081404 (2012)) describing the linear propagation of a charge with spin along the axis of a helical charge distribution. We explore different parameter regions and show that a strong negative spin polarization as observed in the previously mentioned experiments can be obtained with reasonable values of both the electronic coupling elements and the helical field induced spin-orbit interaction.
CRIS-Team Scopus Importer:2023-03-20